Alginate-Based Microbeads from Encapsulated Cosmos Caudatus K. Extracts: In Vitro Release Profiles - Fadlila, Safina Samara Nur; Puspita, Oktavia Eka; Ningsih, Zubaidah; Safitri, Anna (EKSAKTA: Journal of Sciences and Data Analysis, 2024)
This study aims to investigate the microencapsulation of C. caudatus K. leaves extract under optimal conditions, focusing on its potential as a therapeutic option for type 2 diabetes. In order to determine the inhibitory effect on the α-amylase enzyme, which plays a crucial role in glucose metabolism, biological activity assays were performed. The procedure of effectively encapsulating the substance was achieved at a pH level of 6 using sodium alginate at a concentration of 2% (w/v), resulting in a 77.2% percentage of encapsulation. The experiment involving the inhibition of α-amylase exhibited an IC50 value of 69.44 ± 0.924 μg/mL, demonstrating the significant biological activity of the microcapsules. The bioactive substances encapsulated in the microcapsules were released during intervals 30-120 min, at pH conditions of 2.2 and 7.4. The release of bioactive substances was only 2.32 % after 120 minutes at a pH of 2.2, whereas it increased to 64.54 % at a pH of 7.4. This discovery indicates that the microcapsules contain the capability to be utilized for the regulated delivery of drugs. The findings of this research demonstrate the potential to develop herbal medicines with therapeutic properties through microencapsulation, providing an excellent opportunity for managing type 2 diabetes.